2023
DOI: 10.1655/herpetologica-d-22-00035
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Crossodactylodes from the Espinhaço Mountain Range, Southeastern Brazil (Anura: Leptodactylidae: Paratelmatobiinae)

Abstract: The bromeligenous genus Crossodactylodes, endemic to the Atlantic Forest domain and the ''campo rupestre'' ecosystem in Brazil, currently comprises five named species. Three additional putatively new species have already been proposed in a recent study based on mitochondrial and nuclear markers. Here we employ phenotypic data to corroborate the distinctiveness of one of these lineages, and describe it as a new species, from the Espinhaço Mountain Range in the municipality of Itamarandiba, state of Minas Gerais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Although every recorded bromeliad was resurveyed during the night, we only found frogs in one of the four predicted areas: a forested patch inside a PA (Figure 3), about 60 km from the original population. Further examination of sampled individuals in the lab revealed that our new record was not a new population of C. itambe, but in fact a new species of the genus Crossodactylodes (recently described by Santos et al, 2023). This PA has high altitude (1519-1620 m a.s.l.)…”
Section: Searching For New Populations Of Frogsmentioning
confidence: 76%
“…Although every recorded bromeliad was resurveyed during the night, we only found frogs in one of the four predicted areas: a forested patch inside a PA (Figure 3), about 60 km from the original population. Further examination of sampled individuals in the lab revealed that our new record was not a new population of C. itambe, but in fact a new species of the genus Crossodactylodes (recently described by Santos et al, 2023). This PA has high altitude (1519-1620 m a.s.l.)…”
Section: Searching For New Populations Of Frogsmentioning
confidence: 76%